Indigenous people and the Pilbara mining boom : a baseline for regional participation - Taylor, J. (John), 1953- (Research monograph (Australian National University. Centre for Aboriginal Economic Policy Research), 2006)
"The largest escalation of mining activity in Australian history is currently underway in the Pilbara region of Western Australia. Pilbara-based transnational resource companies recognise that major social and economic impacts on Indigenous communities in the region are to be expected and that sound relations with these communities and the pursuit of sustainable regional economies involving greater Indigenous participation provide the necessary foundations for a social licence to operate. This study examines the dynamics of demand for Indigenous labour in the region, and the capacity of local supply to respond. A special feature of this study is the inclusion of qualitative data reporting the views of local Indigenous people on the social and economic predicaments that face them. The basic message conveyed is that little has been achieved over the past four decades in terms of enhancing Indigenous socioeconomic status in the Pilbara. On the basis of planned economic development and corporate interest in pursuing Indigenous engagement, progress is now possible but major efforts are required from all interested stakeholders (Indigenous organisations, miners and governments) in order to ensure that this occurs."--Publisher's description